Identify known and novel candidate genes associated with backfat thickness in Duroc pigs by large-scale genome-wide association analysis. (16th January 2022) - Ding, Rongrong; Zhuang, Zhanwei; Qiu, Yibin; Ruan, Donglin; Wu, Jie; Ye, Jian; Cao, Lu; Zhou, Shenping; Zheng, Enqin; Huang, Wen; Wu, Zhenfang; Yang, Jie
Abstract: Backfat thickness (BFT) is complex and economically important traits in the pig industry, since it reflects fat deposition and can be used to measure the carcass lean meat percentage in pigs. In this study, all 6, 550 pigs were genotyped using the Geneseek Porcine 50K SNP Chip to identify SNPs related to BFT and to search for candidate genes through genome-wide association analysis in two Duroc populations. In total, 80 SNPs, including 39 significant and 41 suggestive SNPs, and 6 QTLs were identified significantly associated with the BFT. In addition, 9 candidate genes, including a proven major gene MC4R, 3 important candidate genes ( RYR1, HMGA1, and NUDT3 ) which were previously described as related to BFT, and 5 novel candidate genes ( SIRT2, NKAIN2, AMH, SORCS1, and SORCS3 ) were found based on their potential functional roles in BFT. The functions of candidate genes and gene set enrichment analysis indicate that most important pathways are related to energy homeostasis and adipogenesis. Finally, our data suggest that most of the candidate genes can be directly used for genetic improvement through molecular markers, except that the MC4R gene has an antagonistic effect on growth rate and carcass lean meat percentage in breeding. Our results will advance our understanding of the complex genetic architecture of BFT traits and laid the foundation for additional genetic studies to increase carcass lean meat percentage of pig through marker-assisted selection and/or genomic selection. Lay Summary: Backfat thickness (BFT) is a complex and economically important trait in the pig industry because it reflects fat deposition and can be used to measure the carcass lean meat percentage in pigs. In this study, two Duroc populations were genotyped using SNP chips, and genome-wide association analysis was used to identify SNPs and candidate genes related to BFT. A number of genetic markers and candidate genes including MC4R, RYR1, HMGA1, NUDT3, SIRT2, NKAIN2, AMH, SORCS1, and SORCS3 were identified to be significantly related to BFT. Our data suggest that many of the candidate genes can be directly used for genetic improvement through molecular markers. Abstract : New genetic markers and candidate genes are identified in a genome-wide association study to be related to backfat thickness in Duroc pigs.